Milk sauce and paprika : migration, childhood and memories of the interwar Belgian-Hungarian child relief project - Hajtó, Vera (Leuven University Press, 2016)
Children who migrated without their families were noteworthy participants of interwar European migration history. 'Milk Sauce and Paprika' tells the story of Hungarian children who were sent to Belgium in the framework of a humanitarian project between 1923 and 1927. Based on a wide variety of sources such as official documents, contemporary newspapers, photographs, family correspondences, biographies and interviews, this book examines the history of the Belgian-Hungarian child relief project and describes its social and cultural impacts on the families involved in both countries. This compelling story of one of the first mass European child migration movements offers new insights in the dynamics of national and religious communities. Furthermore, it sheds light on intimate family life and contemporary habits and values regarding parenting and co-parenting in the interwar period. Cutting across national and cultural borders, this monograph connects individual and collective memory with the experiences of childhood and migration.